Effects of sprint interval training and body weight reduction on power to weight ratio in experienced cyclists - Lunn, W. R.; Finn, J. A.; Axtell, R. S. (The Journal of Strength and Conditioning Research, 2009)
The purpose of this study was to determine the effect of supramaximal sprint interval training (SIT), body weight reduction, and a combination of both treatments on peak and average anaerobic power to weight ratio (PPOan:Wt, APOan:Wt) by manipulating peak and average anaerobic power output (PPOan, APOan) and body weight (BW) in experienced cyclists. Participants (N = 34, age = 38.0 ± 7.1 years) were assigned to 4 groups for a 10-week study. One group performed twice-weekly SIT sessions on a cycle ergometer while maintaining body weight (SIT). A second group did not perform SIT but intentionally reduced body weight (WR). A third group simultaneously performed SIT sessions and reduced body weight (SIT+WR). A control group cycled in their normal routine and maintained body weight (CON). The 30-second Wingate Test assessed pretest and posttest POan:Wt scores. There was a significant mean increase (p < 0.05) from pretest to posttest in PPOan:Wt and APOan:Wt (W/kg) scores in both SIT (10.82 ± 1.71 to 11.92 ± 1.77 and 8.05 ± 0.64 to 8.77 ± 0.64, respectively) and WR (10.33 ± 2.91 to 11.29 ± 2.80 and 7.04 ± 1.45 to 7.62 ± 1.24, respectively). PPOan and APOan (W) increased significantly only in SIT (753.7 ± 121.0 to 834.3 ± 150.1 and 561.3 ± 62.5 to 612.7 ± 69.0, respectively). Body weight (kg) decreased significantly in WR and SIT + WR (80.3 ± 13.7 to 75.3 ± 11.9 and 78.9 ± 10.8 to 73.4 ± 10.8, respectively). The results demonstrate that cyclists can use SIT sessions and body weight reduction as singular training interventions to effect significant increases in anaerobic power to weight ratio, which has been correlated to enhanced aerobic cycling performance. However, the treatments were not effective as combined interventions, as there was no significant change in either PPOan:Wt or APOan:Wt in SIT + WR.